The Effect of Trade Wars, Risk Management Score, and Diversification Strategy on Operating Margin IDX-Listed Companies - Natali Ikawidjaja (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the impact of trade wars on the operational strategies of companies listed on the Indonesia Stock Exchange (IDX), highlighting the role of risk management as a mitigation mechanism. Global trade tensions, such as those between the United States and China, have created significant uncertainty in the flow of goods and exchange rates, directly and indirectly impacting the operational stability of companies in developing countries, including Indonesia. This study uses a mixed methods approach combining quantitative and qualitative analysis. Quantitative data were collected from company annual reports for the 2018–2023 period and analyzed using OLS linear regression to examine the effect of the trade war index, risk management score, and diversification strategy on operating margin. Meanwhile, qualitative analysis was conducted through a content study of annual reports and sustainability reports to capture companies’ strategic narratives in the face of external pressures. The results show that all three independent variables significantly influence operating margin. Companies with robust risk management systems and clear diversification strategies are able to maintain more stable performance amidst global tensions. These findings strengthen contingency theory and strategic risk management and provide an important contribution to the study of corporate resilience in an era of global uncertainty.